2014
DOI: 10.1097/gme.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical exercise on health-related quality of life and blood lipids in perimenopausal women

Abstract: Physical exercise can substantially reduce menopausal symptoms and improve blood lipid status and body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 43 publications
0
34
0
3
Order By: Relevance
“…38 The North American Menopause Society and the UK's Royal College of Obstetricians and Gynecologists recommend aerobic exercise and regular exercise as an intervention for treating mild to moderate menopausal symptoms in perimenopausal women. 39 The top three menopauserelated symptoms in Chinese women include fatigue, irritability, and arthralgia. 39 In a 12-week randomized, controlled trial of brisk walking for 30 minutes at least three times a week, women who exercised reported decreased paresthesia, insomnia, irritability, arthralgia, and fatigue.…”
Section: Short Term Benefits Of Exercise Symptom Reliefmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The North American Menopause Society and the UK's Royal College of Obstetricians and Gynecologists recommend aerobic exercise and regular exercise as an intervention for treating mild to moderate menopausal symptoms in perimenopausal women. 39 The top three menopauserelated symptoms in Chinese women include fatigue, irritability, and arthralgia. 39 In a 12-week randomized, controlled trial of brisk walking for 30 minutes at least three times a week, women who exercised reported decreased paresthesia, insomnia, irritability, arthralgia, and fatigue.…”
Section: Short Term Benefits Of Exercise Symptom Reliefmentioning
confidence: 99%
“…39 The top three menopauserelated symptoms in Chinese women include fatigue, irritability, and arthralgia. 39 In a 12-week randomized, controlled trial of brisk walking for 30 minutes at least three times a week, women who exercised reported decreased paresthesia, insomnia, irritability, arthralgia, and fatigue. In addition, weight, BMI, waist circumference, triglycerides, and total cholesterol were significantly improved in the exercise intervention group.…”
Section: Short Term Benefits Of Exercise Symptom Reliefmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27][28] Seven of the studies were published in journals, [21][22][23][24][25][26][27] whereas one was a dissertation. 28 None of the studies fulfilled all the high-quality requirements.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Several recent studies have shown the effects of walking on body weight and body composition in perimenopausal and postmenopausal women [18][19][20][21][22][23][24][25][26][27][28] ; however, to our knowledge, there has not been a systematic evaluation of the effects of walking on body weight and fat distribution in perimenopausal and postmenopausal women. A meta-analysis is an approach in which individual study outcomes are quantitatively combined to arrive at overall conclusions regarding a body of research.…”
mentioning
confidence: 99%